2018
DOI: 10.3390/agriculture8030042
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting Waste Heat from Combine Harvesters to Damage Harvested Weed Seeds and Reduce Weed Infestation

Abstract: Weeds are mainly controlled with herbicides in intensive crop production, but this has resulted in increasing problems with herbicide-resistant weeds and public concerns about the unwanted side-effects of herbicide use. Therefore, there is a need for new alternative methods to reduce weed problems. One way to reduce weed infestation could be to collect or kill weed seeds produced in the growing season. Crop and weeds are harvested simultaneously with the combine harvester, but most of the weed seeds are return… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…At the moment, a new system using the heat source from the exhaust gas of the combine harvester to kill weed seeds is under consideration (Jakobsen et al 2019). The intention is to bring the chaff fraction and contained weed seeds into contact with hot exhaust gases to kill the weed seeds before returning this material to the field (Andreasen et al 2018;Glasner et al 2018;Jakobsen et al 2019). The critical question is how much of the total weed seed production in a growing season is retained on the weed plants at crop harvest.…”
Section: Introductionmentioning
confidence: 99%
“…At the moment, a new system using the heat source from the exhaust gas of the combine harvester to kill weed seeds is under consideration (Jakobsen et al 2019). The intention is to bring the chaff fraction and contained weed seeds into contact with hot exhaust gases to kill the weed seeds before returning this material to the field (Andreasen et al 2018;Glasner et al 2018;Jakobsen et al 2019). The critical question is how much of the total weed seed production in a growing season is retained on the weed plants at crop harvest.…”
Section: Introductionmentioning
confidence: 99%
“…We have now shown that a large proportion of seeds produced during the growing season of common weed species potentially can be collected and removed or destroyed [43][44][45] by a combine harvester at crop harvest. The next step will be to test how large a fraction of this potential a combine harvest actually collects, as it depends on several factors such as harvest height and the number of seeds dropping to the soil surface under the harvesting process.…”
Section: Discussionmentioning
confidence: 99%
“…The experiments were repeated later (series 2), but then the temperature could not be lowered to less than 85 • C because the ambient temperature had increased by 13 • C. We prevented temperature variation by keeping the throttle at the position that resulted in the desired temperatures, and we monitored the exhaust gas temperature with a thermometer continuously during the experiments (Table 2). Considering both the time it takes seeds to pass through the combine harvester and the risk of fire at high exhaust gas temperatures, we chose three temperatures for the heat treatment of the seeds based on earlier studies [23]. Seeds in the round pincer filter (Figure 1) were exposed to three temperatures (75 • C or 85 • C, 110 • C, and 140 • C) and three durations (2, 4, and 6 s).…”
Section: Methodsmentioning
confidence: 99%